2022
DOI: 10.48550/arxiv.2201.04997
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strangeness $S = -2$ baryon-baryon interactions and femtoscopic correlation functions in covariant chiral effective field theory

Abstract: We study the baryon-baryon interactions with strangeness S = −2 and corresponding momentum correlation functions in leading order covariant chiral effective field theory. The relevant low energy constants are determined by fitting to the latest HAL QCD simulations, taking into account all the coupled channels. Extrapolating the so-obtained strong interactions to the physical point and considering both quantum statistical effects and the Coulomb interaction, we calculate the ΛΛ and Ξ − p correlation functions w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 90 publications
(156 reference statements)
0
6
0
Order By: Relevance
“…(See also Ref. [39] in this context.) There is no visible cusp for NLO16 because here the (𝐼 = 1) 3 𝑆 1 interaction is weaker/repulsive [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(See also Ref. [39] in this context.) There is no visible cusp for NLO16 because here the (𝐼 = 1) 3 𝑆 1 interaction is weaker/repulsive [7].…”
Section: Resultsmentioning
confidence: 99%
“…There a 𝑆 = −2 potential established from lattice QCD simulations by the HAL QCD Collaboration [38] has been employed. A recent study of Liu et al [39] uses a LO interaction based on covariant 𝜒EFT that was fitted to the phase shifts of the aforementioned HAL QCD potential. In this case similar 𝑅 values as those adopted by us for our NLO19 results seem to be preferred for getting agreement with the ALICE data and not those of [32].…”
Section: Resultsmentioning
confidence: 99%
“…At leading order (LO), the covariant scheme has been successfully employed to study the nucleon-nucleon scattering [22,[31][32][33][34] and hyperon-nucleon scattering [35][36][37][38][39][40][41]. In particular, We showed that in Ref.…”
Section: Brief Review Of Leading Order Resultsmentioning
confidence: 99%
“…In the covariant ChEFT, Lorentz covariance is maintained by employing the covariant chiral Lagrangians, the full form of Dirac spinors, and the relativistic scattering equation (the Kadyshevsky equation). It has been shown that the covariant ChEFT approach can provide reasonable descriptions of octet baryon-octet baryon interactions already at LO, including all the systems from strangeness S = 0 to S = −4, at least in the low energy region [4][5][6][7][8][9][10][11][12][13][14]. 8 A recent study [11] showed that one could reproduce both the physical 1 S 0 and 3 S 1 -3 D 1 and the lattice QCD nucleon-nucleon partial wave phase shifts fairly well.…”
Section: Introductionmentioning
confidence: 99%
“…. More details about the covariant ChEFT approach can be found in [4][5][6][7][8][9][10][11][12][13][14][15].…”
mentioning
confidence: 99%